EFEKTIVITAS ANTIBAKTERI MADU DAN PROPOLIS TERHADAP BAKTERI STAPHYLOCOCCUS AUREUS - Mentari, Ika Nurfajri (Politeknik Medica Farma Husada Mataram, 2018)
This research was conducted based on several things, that is because it is one of the health problems, especially the problem of nosocomial infection that occurred in the hospital. The presence of chemical antibiotic resistance to Staphylococcus aureus bacteria and the use of natural antibiotics that are believed to prevent or kill a bacterium without side effects on the host. This research was conducted at Biomedical Research Unit Laboratory of West Nusa Tenggara Province General Hospital.The purpose of this study was to determine the difference of antibacterial effectiveness of honey and propolis against Staphylococcus aureus bacteria. Some concentrations ranging from 100%, 75%, 50% and 25% with ciprofloxacin antibiotics as positive controls.This research is true experimental research using diffusion method with amount of 12 MHA media (Mueller Hinton Agar) which is suspension of Staphylococcus aureus bacteria. In each medium made 5 holes 8 mm diameter wells. Then honey and propolis that have been made concentrations ranging from 100%, 75%, 50% and 25% dripped into the well as much as 50 Î¼l and antibiotics ciprofloxacin affixed into the well. Subsequently incubated for 24 hours at 370C. The difference in antibacterial effectiveness of honey and propolis can be known by measuring the diameter of the inhibition zone formed on MHA media, using a ruler. Data obtained from the results of the study were analyzed by statistical test using Kruskal-Wallis Test and Mann-Whitney Test.The result of Kruskal-Wallis Test test shows that there is a significant difference of constraint zone from some concentration, either from honey or propolis (P â¤ 0,05). Mann-Whitney Test showed a significant difference in antibacterial effectiveness of honey and propolis against Staphylococcus aureus (P â¤0,05) bacteria. The conclusion of this study is that honey and propolis have different antibacterial power from 100%, 75%, 50% and 25% concentration, as well as from the antibacterial effectiveness of honey and propolis in the process of inhibiting the growth of Staphylococcus aureus bacteria.